Model Pembelajaran Teknik Lompat Jangkit Dengan Metode Bermain di Sekolah Dasar - R Sudarwo; Yohanes Yohanes (Jurnal Pendidikan dan Kebudayaan, 2011)
This study aims to describe how far the application of learning models jump technique transmissible by playing methods to improve student achievement in elementary school. Results showed that students more actively involved in learning, they do jump transmissible enthusiastic while playing, so it can be concluded students feel happy to do the jump transmissible by playing methods, as well as students make the mistake of awareness and responsibility of learners doing push ups with pleasure as punishment without being asked by the teacher.